Finite Element Modeling of the Behavior of a Hollow Cylinder in a Hydrogen-Containing Environment (Fracture and Structural Integrity, 2019)
The two main research orientations on the problem of hydrogen embrittlement are examined: the study of fundamental principles and the disclosure of micromechanisms and the relation between hydrogen embrittlement and metal aging; the development of models and methods for predicting the kinetics of change in stress-strain state and for evaluating the longevity of structures subjected to hydrogen embrittlement. The state of the problem of hydrogen embrittlement of metals in the first direction is briefly analyzed. More attention is paid to the importance of predicting the behavior of charged metal structures under the influence of hydrogen embrittlement. We then examine the use of finite element modeling using the ANSYS software to compute the calculation analysis of a hollow cylinder subjected to internal and external pressures and hydrogen embrittlement. The cylinder material is nonlinear elastic and its properties depend on the hydrogen concentration at each point of the cylinder. Consideration is given to the influence of the rigidity of the stress state and the hydrogen concentration on the diffusion kinetics of hydrogen in the cylinder body.  The problem is solved in time steps. The distributions of the hydrogen concentration and the stresses for a quarter of the volume of the cylinder are given, as well as the graphs of these values ​​according to the thickness of the wall of the cylinder at different times.It is shown that the ANSYS software package adapted to the resolution of such problems can model the behavior of different structures in a hydrogen-containing environment, taking into account the effects caused by both the influence of hydrogen on mechanical properties of the material and by the stress state of the structures, as well as by the influence of the stress state on the interaction kinetics of hydrogen with the structures.
Keywords: Hydrogen embrittlement; Hollow cylinder; Physical nonlinearity; Hydrogen effect; Finite element modeling